2015
DOI: 10.1111/fare.12103
|View full text |Cite
|
Sign up to set email alerts
|

Child and Family Resilience: A Call for Integrated Science, Practice, and Professional Training

Abstract: Science and practice focused on child resilience and family resilience have deep and intertwined roots, yet there have been surprisingly few efforts to systematically integrate the theory, findings, and implications of these two traditions of work. In this article, the authors discuss parallels in concepts and processes that link the sciences of child and family resilience and the potential of relational developmental systems theory to provide an integrative framework for understanding and promoting resilience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
223
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(245 citation statements)
references
References 85 publications
(132 reference statements)
11
223
0
11
Order By: Relevance
“…Research with juvenile sex offenders found that they were more likely than juvenile non-sex offenders and juvenile non-delinquents to have fewer attachments to peers and school (Minor and Crimmins 1995). Using a resilience framework (Masten and Monn 2015), there is value, however, in conceptualizing these factors as protective against violence, controlling for the influence of other negative exposures, because this conceptualization can more readily inform prevention efforts. Resilience in this context refers to the capacity of an individual to successfully adapt to challenges and involves interplay with other influences (e.g., family, community) (Masten and Monn 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research with juvenile sex offenders found that they were more likely than juvenile non-sex offenders and juvenile non-delinquents to have fewer attachments to peers and school (Minor and Crimmins 1995). Using a resilience framework (Masten and Monn 2015), there is value, however, in conceptualizing these factors as protective against violence, controlling for the influence of other negative exposures, because this conceptualization can more readily inform prevention efforts. Resilience in this context refers to the capacity of an individual to successfully adapt to challenges and involves interplay with other influences (e.g., family, community) (Masten and Monn 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yet resilience can be also inferred from evidence that the system is "likely" to respond well when given the resources and adaptive capabilities available to the system. Efforts to prepare individuals, families, communities, and other systems for anticipated challenges often have the goal of building system capacity for positive responses to disturbances [15]. For the purpose of the present study, resilience will be defined as the tendency to overcome factors that place one at risk for psychological dysfunction and to adjust positively in the aftermath of a potentially traumatic event [16].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Masten and Monn (2015) pointed to the importance of child and family resilience as an important consideration in contemporary discussions of adaptive behaviour. However, a review of the literature indicates few efforts to date to systematically integrate the theory, findings, and implications of these two areas.…”
Section: Survival: the Role Of Play In Supporting Adaptive Behavioursmentioning
confidence: 99%